2023
DOI: 10.2196/49324
|View full text |Cite
|
Sign up to set email alerts
|

Large Language Models for Therapy Recommendations Across 3 Clinical Specialties: Comparative Study

Theresa Isabelle Wilhelm,
Jonas Roos,
Robert Kaczmarczyk

Abstract: Background As advancements in artificial intelligence (AI) continue, large language models (LLMs) have emerged as promising tools for generating medical information. Their rapid adaptation and potential benefits in health care require rigorous assessment in terms of the quality, accuracy, and safety of the generated information across diverse medical specialties. Objective This study aimed to evaluate the performance of 4 prominent LLMs, namely, Claude-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The progression from unimodal to multimodal AI represents an essential and imperative advancement to effectively exploit the complete capabilities of AI in the health care. A 10-point strategy to evaluate and ease the implementation of LLM in rehabilitation is proposed in Table 2, summarizing current recommendations 7,9,14,20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The progression from unimodal to multimodal AI represents an essential and imperative advancement to effectively exploit the complete capabilities of AI in the health care. A 10-point strategy to evaluate and ease the implementation of LLM in rehabilitation is proposed in Table 2, summarizing current recommendations 7,9,14,20 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an exploration of LLMs for therapy recommendations in ophthalmology, orthopedics, and dermatology revealed proficiency but raised concerns about content quality and potential harm 9 …”
Section: Large Language Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversational AI models across different medical specialties like ophthalmology, orthopedics, and dermatology, found significant differences in the quality and safety of the medical advice provided (40). Furthermore, research by Maillard and colleagues revealed that GPT-4 occasionally produces incorrect and, at times, detrimental medical guidance and treatment strategies (31).…”
Section: Al On Variousmentioning
confidence: 99%
“…It is essential to keep checking and improving AI models to make sure they can create medical information that is trustworthy and safe, primarily when used for mental health therapies and other medical uses. Doing this is critical to making people trust these models and finding them helpful in different medical areas [ 16 ].…”
Section: Introductionmentioning
confidence: 99%